2011
DOI: 10.1063/1.3518457
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast vibrational dynamics and spectroscopy of a siloxane self-assembled monolayer

Abstract: Time and frequency domain sum-frequency generation (SFG) were combined to study the dynamics and structure of self-assembled monolayers (SAMs) on a fused silica surface. SFG-free induction decay (SFG-FID) of octadecylsilane SAM in the CH stretching region shows a relatively long time scale oscillation that reveals that six vibrational modes are involved in the response of the system. Five of the modes have commonly been used for the fitting of SFG spectra in the CH stretching region, namely the symmetric stret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 53 publications
4
52
2
Order By: Relevance
“…To fit the normalized Vis-SFG spectrum at the Al 2 O 3 /H 2 O interface, the well-known equation that describes the SFG process by a broad-band infrared pulse and a visible pulse is used. 17…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…To fit the normalized Vis-SFG spectrum at the Al 2 O 3 /H 2 O interface, the well-known equation that describes the SFG process by a broad-band infrared pulse and a visible pulse is used. 17…”
mentioning
confidence: 97%
“…17,18 This limitation may be overcome if vSFG experiments are carried out in the time domain, i.e., free induction decay vSFG (FID-SFG), with the condition that time domain measurements have higher temporal resolution compared to the vibrational dynamics of the interface. Additionally, time domain vSFG is more sensitive to inhomogeneous broadenings simultaneously present in frequency domain vSFG spectra.…”
mentioning
confidence: 99%
“…These studies demonstrated the usefulness of multi-dimensional spectroscopy regarding the resolution of intermolecular interactions, 17,24 vibrational dephasing and relaxation, as well as spectral diffusion from samples at interfaces. 16,19,49 For instance, variations in spectral diffusion and vibrational relaxation dynamics have been discussed between octahedral rheniumcarbonyl photocatalysts at silica interfaces and in bulk solution, 16,49 revealing that spectral diffusion at surfaces is slower than in bulk solution. This effect was attributed to interactions of molecules within the monolayer and variations in structural evolution.…”
Section: General Context Of Spectral Diffusion At Interfacesmentioning
confidence: 99%
“…Regarding spectroscopic investigations of MLs at interfaces, central points of interest are represented by details of binding configurations or influences of the environmental interactions on molecular properties as compared to the case of isolated molecules in bulk solution. [16][17][18][19] This is because the structure of molecules in MLs is often influenced by intermolecular interactions within the densely packed aggregate. 20,21 In addition, solvent molecules directly at the interface are likely to exhibit differences in their properties such as hydrogen-bonding networks and dipolar orientation as compared to the bulk solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation